Implementasi Tugas Pokok dan Fungsi Balai Pemasyarakatan Denpasar dalam Bimbingan Terhadap Klien Anak - Dwik Aditya Pramana; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2024)
Children in conflict with the law must be protected as the nation's successor, therefore the Correctional Center has an important role in guiding the child to be accepted back into society. The formulation of this research problem is , How is the implementation of the main tasks and functions of Denpasar Correctional Center? Factors that hinder the process of guidance to child clients at Denpasar Correctional Center? This research is of the empirical legal type, with a data analysis approach using descriptive methods. The results of the study show that the main tasks and functions of the Correctional Center in providing guidance to juvenile clients have been implemented properly, through two forms of guidance mechanisms. The conclusion of this study, there are obstacles by the Correctional Center in conducting guidance, these obstacles consist of internal obstacles and external obstacles. External barriers consist of communication problems. While external problems consist of the lack of availability of facilities and infrastructure. The author's suggestion in this study is that good coordination between legal agencies and the availability of adequate facilities and infrastructure are needed, so that the guidance process can be carried out properly.